Comparing the tidally influenced facies in the Tonganoxie sandstone in northeastern Kansas with modern analogs from Turnagain Arm of Cook Inlet, Alaska, USA - Al-Hashim, Mansour H. (Kansas State University, 2009)
Abstract This study compares the tidally influenced facies found within the Tonganoxie Sandstone Member (Stranger Formation, Douglas Group) (Upper Pennsylvanian) of northeastern Kansas with similar facies directly observed in the upper intertidal mudflats of Turnagain Arm of Cook Inlet (Alaska, USA). The two settings contain strikingly similar facies that are characteristic of upper macrotidal estuaries with a strong influence of tidal activities. Identical aspects and features found within both settings include rhythmic vertical variation in stratum thicknesses (cyclic tidal rhythmites), high estimated sedimentation and aggradation rates, and biogenic and physical sedimentary structures (e.g., drag marks, raindrop impressions, arthropod traces and tetrapod trackways, zigzag burrows, runoff washouts, and upright trees, among others). Tidal rhythmites are the most important evidence that is indicative of the tidal influence on the depositional processes of these two study areas. Such cyclic tidal rhythmites have been reported and described from several Carboniferous settings in the eastern USA. Modern analogs to these Carboniferous rhythmites are usually found within upper macrotidal estuarine depositional environments, especially within fluvio-estuarine transitional zones. These environments are distributed over a wide range of modern latitudes. Using cyclic tidal rhythmites as modern analogs for interpreting similar ancient facies is a powerful tool for paleogeographic and paleoenvironmental reconstructions, although it is somewhat a new approach.
Keywords: Incised paleovalley fills; Tonganoxie Sandstone; Tidal influence; Turnagain Arm; Modern analogs; Sedimentary structures; Geology (0372)